Health Belief Model: Health Preventive Behavior of Sexually Transmitted Infection in Female Sex Workers in Surakarta - Yenni Apriana Wulandari; Nunuk Suryani; Eti Poncorini (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Sexually Transmitted Infection (STI), such as HIV/ AIDS, is a public health problem. The prevalence of HIV in Indonesia in 2014 was 32,711 cases, and the prevalence of AIDS was 5,494 cases. In 2015 the Municipality Health Office of Surakarta found 71 cases of STI, consisting of 18 cases of HIV, 47 cases of AIDS, and 6 cases of Siphilis. A female sex worker may have several sexual partners per day. As studies have shown, female sex workers have 12 times higher risk of HIV infection than loyal housewife. Condom use can reduce up to 85% risk of HIV transmission. This study aimed to investigate the factors affecting STI preventive behavior among female sex workers in Surakarta, using Health Belief Model (HBM).Subjects and Method: This was an observational analytic study with cross-sectional design. This study was conducted in Banjarsari, Surakarta, Indonesia, from August to October 2016. A total of 130 female sex workers were selected at random. The independent variables were perceived susceptibility, perceived severity, perceived benefit, perceived barrier, cues to action, and self-efficacy. The dependent variable was STI preventive behavior. The data was collected by questionnaire and analyzed by logistic regression model.Results: Perceived susceptibility (OR=7.45; CI=95%; 1.61 to 49.89; p=0.012), severity (OR=4.02; CI=95%; 1.14 to 14.17; p=0.310), benefit (OR=5.63; 95% CI; 1.10 to 28.91; p=0.390), barrier (OR = 0.18; 95% CI; 0.02 to 0.70; p=0,018), cues to action (OR=7.32; CI=95%; 1,18 to 29.29; p=0.050), self-efficacy (OR=5.10; CI=95%; 1.10 to 23.58; p=0.370), had positive effects on STI preventive behavior.Conclusion: Perceived susceptibility, severity, benefit, barrier, cues to action, self-efficacy, had positive effects on STI preventive behavior. This study supports the applicability of the HBM constructs when they are used to explain factors affecting STI prevention behavior.Keywords: Health Belief Model, sexually transmitted infection, female sex workerCorrespondence: Yenni Apriana Wulandari. Masters Program in Public Health, Sebelas Maret University, SurakartaJournal of Health Promotion and Behavior (2016), 1 (2): 70-78https://doi.org/10.26911/thejhpb.2016.01.02.02